Tafenoquine and its potential in the treatment and relapse prevention of Plasmodium vivax malaria: the evidence to date - Ebstie YA; Abay SM; Tadesse WT; Ejigu DA (Dove Medical Press, 2016)
Yehenew A Ebstie,1,* Solomon M Abay,2,* Wondmagegn T Tadesse,3 Dawit A Ejigu4 1Department of Microbiology, Immunology and Parasitology, 2Department of Pharmacology, 3Department of Pharmacology and Clinical Pharmacy, School of Medicine, College of Health Sciences, Addis Ababa University, 4Department of Pharmacology, St Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia *These authors contributed equally to this work Abstract: Despite declining global malaria incidence, the disease continues to be a threat to people living in endemic regions. In 2015, an estimated 214 million new malaria cases and 438,000 deaths due to malaria were recorded. Plasmodium vivax is the second most common cause of malaria next to Plasmodium falciparum. Vivax malaria is prevalent especially in Southeast Asia and the Horn of Africa, with enormous challenges in controlling the disease. Some of the challenges faced by vivax malaria-endemic countries include limited access to effective drugs treating liver stages of the parasite (schizonts and hypnozoites), emergence/spread of drug resistance, and misperception of vivax malaria as nonlethal. Primaquine, the only 8-aminoquinoline derivative approved by the US Food and Drug Administration, is intended to clear intrahepatic hypnozoites of P. vivax (radical cure). However, poor adherence to a prolonged treatment course, drug-induced hemolysis in patients with glucose-6-phosphate dehydrogenase deficiency, and the emergence of resistance make it imperative to look for alternative drugs. Therefore, this review focuses on data accrued to date on tafenoquine and gives insight on the potential role of the drug in preventing relapse and radical cure of patients with vivax malaria. Keywords: vivax malaria, radical cure, schizonts, hypnozoite, primaquine